KEMATIAN PERINATAL DI BLU RSU PROF. DR. R. D. KANDOU MANADO - Tumundo, Mercy; Tendean, Hermie; Suparman, Eddy (eBiomedik, 2013)
Abstract: Perinatal death is a big problem especially in a developing country. Some of the hospitals in Indonesia have declared that the number of perinatal death in developing countries is higher than in  developed countries. The purpose of this research is to determine the incidence of the factors that affecting perinatal mortality at Prof. DR. R. D. Kandou General Hospital Manado. This research used retrospective descriptive method through medical records of perinatal deaths patients. There were 164 cases of perinatal deaths found where 109 cases still births and 55 cases were early neonatal deaths in 2011, so the number of perinatal mortality rate was 40.17 per mil. The highest number of perinatal death was from multigravide mother, mother with age  ≥ 35 years old, spontaneous parturition. There were unknown caused of still births cases (77,06%) and sepsis in early neonatal deaths. The normal birth weight is also with most include of perinatal deaths. Keywords: still birth, early neonatal death, perinatal deaths, perinatal mortality rate.     Abstrak: Kematian perinatal merupakan masalah besar khususnya di negara sedang berkembang. Beberapa rumah sakit pendidikan di Indonesia melaporkan angka kematian perinatal yang tinggi dibandingkan dengan laporan angka kematian perinatal di negara – negara maju yang jumlahnya rendah. Tujuan penelitian untuk mengetahui angka kejadian kematian perinatal serta faktor – faktor yang mempengaruhinya. Penelitian ini menggunakan metode deskriptif retrospektif dengan menggunakan data catatan medik pasien. Hasil penelitian yaitu jumlah kematian perinatal pada tahun 2011 sebanyak 164 kasus dengan 109 kasus lahir mati dan 55 kasus kematian neonatal dini sehingga angka kematian perinatal pada tahun 2011 yaitu 40.17 per mil. Kematian perinatal paling banyak pada ibu multigravida, ibu dengan kelompok usia ≥ 35 tahun, menggunakan jenis persalinan spontan. Pada lahir mati 77.06 % penyebab kematiannya tidak diketahui sedangkan sepsis paling banyak menyebabkan kematian neonatal dini. Berat badan lahir normal juga menjadi salah satu faktor terjadinya kematian perinatal. Kata kunci: lahir mati, kematian neonatal dini, kematian perinatal, angka kematian perinatal.